Metodologia para modelagem de uma câmara de extrapolação em campos padrões secundários de radiação beta - Lucas Fabrício de Araújo (2020)
Technological advancement in the field of ionizing radiation metrology, several questions have arisen regarding the absorbed dose due to beta radiation. Mostly, existing radionuclides are beta and electromagnetic radiation emitters and in many cases, the absorbed dose due to beta radiation exceeds the dose corresponding to the gamma rays. The search for new methodologies of dose measurement and absorbed dose rate due to beta radiation is necessary. The use of computational modeling has allowed significant advances in the optimization of the measurement systems. Since it, besides facilitating and accelerating the analysis, it allows simulating and evaluating the influence of different parameters separately. In addition, it is possible to study new technologies and / or methodologies for the creation of measurement systems. The mathematical model known as the Monte Carlo Method (MMC) uses a sequence of random numbers to simulate a physical phenomenon. Different computational codes were developed using the MC method as the basis for particle transport. The aim of this work was to develop a methodology to model the whole Secondary Beta Standard System (BSS2), with three beta radiation sources and one PTW 23392 extrapolation chamber. For this we used two computational codes, the first is the Monte Carlo N-Particle eXtended (MCNPX) and the second Penetration and ENErgy LOss of Positrons and Electrons (PENELOPE). The main idea is to compare the absorbed dose rate results in $μ$Gy$^{- 1}$ obtained from studies published in the literature for the validation of the developed calibration models. The whole set-up is composed of the PTW-23392 extrapolation chamber, filters and three radioactive sources from different beta-emitting radionuclides which are Kr-85, Sr-90/Y-90 and Pm-147. The articles published by Faria et al., 2015 from the Dosimeter Calibration Laboratory of the Nuclear Technology Development Center (LCD / CDTN) and Polo et al., 2018 from the Instrument Calibration Laboratory of the Institute for Nuclear and Energy Research (LCI / IPEN) were used to validate the developed model. Two equations were used to calculate the dose rate for MC simulations by Faria et al., 2015 and Polo et al., 2018. The difference in dose rate found and compared with those published by Faria et al., 2015 and by Polo et al., 2018 reach up to 4%. The transmission factor was calculated for the source of Kr-85 and difference found was up to 6% and a result with 17% difference and 5% of standard deviation from what was reported in literature. It has been observed that the transport of beta particles in MC codes is extremely costly and complex when compared to electromagnetic waves. This was verified for the two MC codes used in this work.